The effect of the magnetic field distribution of permanent magnets on the trapped field properties of a single domain GdBCO bulk superconductor. (7th January 2020) - Cui, YanLan; Yang, WanMin; Wu, TingTing; Yang, PengTao; Liu, YuGuang; Li, YaJun; Shen, TingTing
Abstract: The trapped field properties of a single domain GdBCO bulk superconductor with a diameter of 32 mm after being magnetized with different permanent magnets under a field cooling state at 77 K have been investigated. The results show that the maximum trapped field of the sample ( Bmtr ) is nearly saturated when the diameter of the permanent magnet d  ≥ 20 mm, but the trapped magnetic flux of the sample (Φ s ) is nearly saturated when d  ≥ 30 mm. This indicates that the largest trapped magnetic flux can be obtained when the size of the permanent magnet is close to that of the sample, and it is not necessary to use a more permanent magnet. In addition, a new and unusual phenomenon is found in that Φ s is greater than the magnetic flux of the permanent magnet (Φ PM ) when the diameter ratio between the permanent magnet and the sample is less than a certain value, such as 0.63 in this experiment. The relationship between Φ s and Φ PM was well expressed as Φ s = 1.6 × 10 − 4 × 1 − e − 1.2 × 10 4 × Φ P M . These results can provide a new method to design and control the trapped field properties of a single domain REBCO bulk superconductor during practical applications.